Our Excursion with Surgical Conduct for Craniopharyngioma - Gurung, Pritam; Shrestha, Bishal; Kayastha, Jessica; Shrestha, Resha; Acharya, Samir; Dhakal, Sudan; Rajbhandhari, Pravesh; Shrestha, Pranaya; Bahadur Basnet, Ranga; Pant, Basant (Annapurna Journal of Health Sciences, 2023)
Background: Craniopharyngioma, an epithelial tumor believed to arise from the remnants of Rathke’s pouch, portray approximately 1.2%-4.4% of all intracranial tumors. Due to its inherent domain in the skull base and its liaison with indispensable neurovascular structure, it has still remained an intimidating contest despite an improved dexterity among the neurosurgeons and refinement in neurosurgical gadgetry.Surgical corridor to come down in favor for is elected by the position of optic chiasm, extension of tumor and development of ACoM or ACA (A1). Methods: A retrospective series study was conducted at Annapurna Neurological Institute and Allied Sciences between January 2016 and August 2021. A total of 20 patients who underwent surgery for histopathologically proven craniopharyngioma was enrolled. Majority of the surgery was performed via a pterional approach while two cases were addressed with a supra ciliary approach and one with a trans nasal trans septal transsphenoidal approach. Result: The age of presentation among our study group ranged from 5 years to 46 years with a mean age of 28.2 years.The most frequent mode of presentation was headache associated with visual disturbances (visual acuity and visual field). Histopathological analysis disclosed an admantinomatous variant 15 cases and a papillary type in 5 cases. The use of Ommaya reservoir in few selective cases was escorted by the cystic ingredient of the lesion. An endeavor to aggressive surgical approach was accomplished, amidst, excision of tumor was subtotal in 9 %, near total in 36 % and gross total in 45 %. Diabetes insipidus was seen in 36%. We had to endure a case of mortality, who lamentably had a massive sub-arachnoid hemorrhage with a colossal PCA territory infarction on arrival. Post operatively, the mass effect evolved on account of PCA territory infarction. Conclusion: The magnitude of resection of the tumor is affected by the extension of tumor, consistency of the lesion and position of optic chiasm. Even with an extensive resection, the prospect of recurrence is inordinately high.